2014
DOI: 10.2478/bpasts-2014-0030
|View full text |Cite
|
Sign up to set email alerts
|

Vertical vibrations of composite bridge/track structure/high-speed train systems. Part 3: Deterministic and random vibrations of exemplary system

Abstract: Abstract. Based on the one-dimensional quasi-exact physical and mathematical modelling of a composite (steel-concrete) bridge/track structure/high-speed train system (BTT), developed in Part 2, advanced computer algorithms for the BTT numerical modelling and simulation as well as a computer programme to simulate vertical vibrations of BTT systems are developed. The exemplary bridge under numerical quasi-static and dynamic analysis, designed according to Polish standards, has a 15.00 m span length and belongs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…3. Simulation of deterministic and random vibrations of the exemplary BTT system is presented in [5,17].…”
Section: Resultsmentioning
confidence: 99%
“…3. Simulation of deterministic and random vibrations of the exemplary BTT system is presented in [5,17].…”
Section: Resultsmentioning
confidence: 99%
“…They resulted in selection of standard elements of the system or proposition of original parts of the considered subsystems, there was verified the accuracy of their operation in the system and, subsequently, after verification with the use of suitably selected simulations CAE and stand tests [3,4,[15][16][17], there was proposed a working project of the modified functional mechanism of the platform and a working project of a prototype version of the loading platform along with 3D documentation of the developed constructional solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Due to a non-linear character of the mapped cooperation of wagon subsystems, including contact phenomena, to perform the strength calculations in the range of static and dynamic [15][16][17], MSC.Nastram, MSC.Marc and LS-Dyna applications [11,12], specialized for analysis of big structures taking into consideration non-linear procedures in the geometric and physical range, were chosen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it causes less traffic congestion by using moving vehicles as a continuous source of energy for the bridge [6,7]. González et al (2010) [8], He et al (2014) [9], and Podworna and Klasztorny (2014) [10] found that the results of dynamic load testing are inevitably influenced by deck conditions, vehicle, and stiffness and form of bridges. Park et al (2005) [11] researched the function of roughness on dynamic load testing through full-scale field tests.…”
Section: Introductionmentioning
confidence: 99%